QUANTITATIVE ANALYSIS OF SALICYLIC ACID BULK SAMPLE USING HYDROTROPIC SOLUBILIZING AGENTS - Patil, Sampatti; Mehta, Preeti; Chavan, Bhagwat (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study was to facilitate titrimetric analysis of poorly water-soluble drug, salicylic acid, using hydrotropic solubilization technique, precluding the use organic solvent. Methods: In the present investigation, poorly water-soluble keratolytic drug, salicylic acid, has been solubilized using nicotinamide (2 M) and sodium benzoate (2 M) as hydrotropic agents for its titrimetric analysis instead of using an organic solvent. Results: There was an enhancement in solubility of salicylic acid in 2 M nicotinamide and sodium benzoate solutions as compared to solubility in distilled water. The mean percent estimation in the bulk drug sample of salicylic acid by Indian Pharmacopeial method is 98.89% while by use of proposed method, i.e., using 2 M nicotinamide and 2 M sodium benzoate solutions were 98.90% and 98.97%, respectively. Compared to sodium benzoate, salicylic acid was found to be more soluble in nicotinamide solution. The results of analysis by proposed method are very close to the results of the standard method. Conclusion: Proposed method is simple, economic, accurate, and reproducible and can be successfully employed in the routine quantitative analysis of drug in bulk drug and dosage form in industries. Keywords: Salicylic acid, Hydrotropy, Sodium benzoate, Nicotinamide, Titrimetry.